El desangramiento latinoamericano: un panorama político contemporáneo sobre la reorganización y la reconfiguración del estado neoliberal - Dudiuk, Pedro (Corporación Universitaria Americana, 2022)
This book was born from a meeting in the city of Barranquilla (Colombia), on the occasion of the event of the American University Corporation (CIID) in 2016. It was an effervescent moment where each of the researchers present there reflected the open wound of Latin America. Through a conversation with the editors of the Corporación Universitaria Americana, the idea emerged to produce a theoretical material where the contemporary realities of various Latin American countries and their struggles to try to continue breathing an unhealthy atmosphere where profound political, social, economic and ideological transformations contaminated our countries.